SOSIALISASI MENGELOLA KEUANGAN USAHA DI PERKUMPULAN PERSATUAN WANITA METHODIST INDONESIA GEREJA METHODIST INDONESIA SUNGAI YORDAN BEKASI - Edison Siregar; Fery Tobing; Riwandari Juniasti Purnama; Lis Sintha Oppusunggu (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2021)
The purpose of Community Service at the Association of Indonesian Methodist Women (PWMI) of the Jordan River Indonesian Methodist Church which consists of housewives is to provide counseling to the housewives about managing business finances. The approach method used is to provide counseling and education about the introduction of side businesses with small capital, Consumer Behavior in the New Normal Era, Break-Even Point Analysis, and How to Manage Business Profits. The results and implications of this Community Service (PkM) activity are the housewives who are members of PWMI can recognize various types of potential side businesses that can be carried out by housewives with small capital and whose mobility is limited. Knowing what challenges will be faced by business owners to survive while changing consumer/community behavior in meeting their needs during the new normal; gain knowledge in business analysis, break-even points and gain knowledge on how to manage business profits/profits so that operating profits can be used for business development. Keywords: financial literacy, housewife, side business